2010
DOI: 10.1016/j.ijsu.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative antibiotic prophylaxis: Adherence to guidelines and effects of educational intervention

Abstract: Although this educational intervention study achieved improvements in indications, choice, and dosing of surgical antimicrobial prophylaxis, it failed to improve prolonged use and total compliance rate, and to lower the costs sufficiently. It will probably provide better results by means of compulsory measures for surgeons to comply with available protocols and guidelines, as well as education programs, in order to change the antibiotic utility habits on surgical prophylaxis and to achieve accurate prophylacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
2
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 25 publications
3
58
2
11
Order By: Relevance
“…Similar finding was observed in cesarean section [12]. Similar finding to ours had been reported in different settings and countries [13][14][15][16]. In our setting, one of the most important challenges was to overcome the previous experience of the staff and provide the best evidence regarding the proper use of antibiotics and to demonstrate the benefits of following it in terms of patient safety and more efficient use of the resources.…”
Section: Discussionsupporting
confidence: 89%
“…Similar finding was observed in cesarean section [12]. Similar finding to ours had been reported in different settings and countries [13][14][15][16]. In our setting, one of the most important challenges was to overcome the previous experience of the staff and provide the best evidence regarding the proper use of antibiotics and to demonstrate the benefits of following it in terms of patient safety and more efficient use of the resources.…”
Section: Discussionsupporting
confidence: 89%
“…The researchers suggested that educational interventions should be augmented with protocols and guidelines in order to improve overall adherence. 15 In the current study, the authors believe that the presence of a clinical pharmacist on the surgery floor was essential in encouraging adherence to the revised antimicrobial prophylaxis guidelines. This clinical pharmacist helped with specific recommendations related to prescribed antibiotics and offered oneto-one and group educational sessions for surgical residents.…”
Section: Discussionmentioning
confidence: 78%
“…As with any programme, education is essential to promote evidence-based practice. However, educational intervention alone is not sufficient to change practice, as demonstrated by Ozgun et al 15 In their study, the educational intervention resulted in improvements in indications, choice and dosage of surgical antimicrobial prophylaxis but did not result in improved prophylaxis use or total compliance rate. The researchers suggested that educational interventions should be augmented with protocols and guidelines in order to improve overall adherence.…”
Section: Discussionmentioning
confidence: 87%
“…Inappropriate antibiotic use in SP can lead to various adverse outcomes, such as selection of resistant micro-organisms and increased costs [8,15,20]. Prevention of inappropriate use must represent a priority in Turkey, as in other countries.…”
Section: Selection Of Antibiotic Inappropriatementioning
confidence: 99%
“…In particular, it must be remembered at antibiotics are not the only option in protection from SSI. A significant improvement can be achieved in prophylaxis with close observation, educational activities, and increasing compliance with guidelines [4,20]. Improvements from 35% to 100%% in terms of dose and duration have been reported with the development and application of common SP protocols in collaboration with the surgical team [4,5].…”
Section: Selection Of Antibiotic Inappropriatementioning
confidence: 99%